Reactualizing Islamic Inheritance Law: Munawir Sjadzali’s Perspective on Gender Equality in Indonesia - Riyanda, Arief Rahman (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This research analyzes Munawir Sjadzali’s reactualization of Islamic inheritance law in Indonesia, motivated by the tension between the 2:1 ratio and modern roles of women. Method: qualitative library research. Approaches: normative-philosophical and sociological. Primary data: Sjadzali’s